Книга о сыре: О его питательных и вкусовых свойствах, ассортименте и способах потребления / В. Л. Бегунов - Бегунов Виталий Львович (Агропромиздат, 1985)
Экземпляры: РБ (20190521) / Инвентарный номер: 30419 / Цена: 8.00 / Авт.знак: Б 37 / ББК: 36.95